Technology and Interactive Media Usage to Support Cyber Wellness Education for Kindergarten - Muniroh Muniroh; Fakhruddin Fakhruddin; Rodiyah Rodiyah; Titi Prihatin (International Conference on Science, Education, and Technology, 2021)
The COVID-19 pandemic changed the education system in Indonesia from Early Childhood to Higher Education through the application of distance learning (DL). It has an impact on the intensity of Early Childhood Education, particularly, to recognize and access technology and interactive media. Young children need to be educated to surf the internet healthily and protect themselves. Cyber wellness refers to the health/well-being of internet users and involves an understanding of online behavior and awareness of how to protect themselves in cyberspace. This study aims to describe the use of technology and interactive media that supports cyber wellness education for kindergarten. The method used in this research was qualitative through interviews and documentation. The results of this study were to create proactive cultures with technology and interactive media in schools to help students become digital learners by 1) paying attention to safety, cultural suitability, needs, interests, and children development, 2) learning to use technology in kindergarten is active, direct, engaging, and empowering children; 3) controlling over children when accessing technology, 4) using technology in class when discussing themes/materials, and when completing assignments or projects given by the teacher, and 5) communicating how to use the internet safely for children with parents.